AN ARTISTIC INTERPRETATION OF THE BOOK LIFE IN THE NIGHT - Mamatqulova Dilafruz (Web of Journals Publishing, 2024)
This article outlines the characteristics, images, styles, and characteristics of Oleksk Hoshimov's novel Life in the Night. Analyzed the location and time characteristics of assyria's events. The writer's artistic skills in creating images have been studied.
Keywords: System, image, exposure, culmination, button, solution, artistic style.